Role of Proteasome Inhibitors in Relapsed and/or Refractory Multiple Myeloma - Leleu, Xavier; Martin, Thomas G.; Einsele, Hermann; Lyons, Roger M.; Durie, Brian G. M.; Iskander, Karim S.; Ailawadhi, Sikander (Clinical Lymphoma Myeloma & Leukemia, 2019)
Proteasome inhibition is an established treatment strategy for patients with multiple myeloma as proteasome inhibitors (PIs) selectively target and disrupt the protein metabolism of aberrant plasma cells. Since the introduction of the first-in-class PIs bortezomib, the therapeutic landscape for multiple myeloma has shifted with the development of next-generation PIs (carfilzomib and ixazomib) and new classes of agents. Treatment with modern combination therapies has been shown to result in deep responses and improved outcomes, and these potent regimens are increasingly used as frontline therapy. As patients continue to live longer with modern frontline therapy, there will be an increased need for effective regimens after initial treatment failure. Several recent studies have shown that treatment with combination therapy incorporating PIs induces deep and durable responses in patients with relapsed and/or refractory multiple myeloma. In this review, we review pivotal data and discuss the role of PIs-based doublet and triplet regimens for the management of relapsed/refractory multiple myeloma in the era of modern combination therapy.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Bortezomib; Carfilzomib; Efficacy; Ixazomib; Safety